Identifying and Correcting Barriers to Successful Inclusive Practices: A Literature Review - Grant, Marquis C.; Jones-Goods, Kimberly Michelle (Journal of the American Academy of Special Education Professionals, 2016)
The inclusion of students with disabilities in the general education classroom is one of the most debated subjects in the field of education today. A review of the literature revealed that while inclusion has been shown to benefit children who receive special education services alongside their non-disabled peers, there are a number of barriers that prevent the practice and procedure of inclusion from being successfully implemented. Lack of teacher training, ineffective instruction, and overall teacher attitudes have been identified as the most prominent barriers to the inclusion process and suggestions for future study indicate that more information to determine the extent to which disabled children are academically, socially and emotionally impacted by those barriers.